Convergence of plant-leafminer associations on two continents - Xiaona Chen; Xiaohua Dai; Qingyun Guo; Charles S. Eiseman (Global Ecology and Conservation)
Plant-herbivore interactions are known to play a pivotal role in shaping global biodiversity and maintaining biosphere stability, with leafminers being recognized as a unique and specialized ecological group within these networks. Despite their ecological significance, plant-leafminer interaction networks have remained understudied, particularly at regional scales. Using up-to-date datasets from Europe and North America, the convergence and divergence of plant-leafminer associations across these continents were examined. Contrary to the hypothesis that significant incongruence would arise due to contrasting biogeographical histories, it was found that plant-leafminer network structures were relatively similar, potentially driven by shared backbone partners or lower taxonomic resolutions. While overall network structures exhibited relative convergence, taxon-specific metrics revealed both similarities and divergences, highlighting the complexity of these interactions. Angiosperms were identified as the dominant host plant phylum, and Lepidoptera emerged as the most prevalent leafminer order. Many leafminers were observed to exhibit narrow host ranges, with plants typically associated with between one and five leafminer genera. However, shared generalist leafminers and host plants, which interact with a wide range of partners, were also present across the two continents. Significant phylogenetic signals were detected on both continents, particularly within subclades such as Spermatophyta, Eudicots + Nymphaeaceae, and Monocots + Eudicots, indicating that closely related plants tend to host similar leafminer communities. This study represents the first systematic comparison of plant-leafminer network structures at the continental scale, providing novel insights into insect-host interaction networks under diverse evolutionary and biogeographic contexts.